Coronavirus Disease 2019 Pandemic: Impact Caused by School Closure and National Lockdown on Pediatric Visits and Admissions for Viral and Nonviral Infections—a Time Series Analysis. (3rd June 2020) - Angoulvant, François; Ouldali, Naïm; Yang, David Dawei; Filser, Mathilde; Gajdos, Vincent; Rybak, Alexis; Guedj, Romain; Soussan-Banini, Valérie; Basmaci, Romain; Lefevre-Utile, Alain; Brun-Ney, Dominique; Beaujouan, Laure; et al.
Abstract: A time series analysis of 871 543 pediatric emergency visits revealed that the coronavirus disease 2019 (COVID-19) lockdown and school closures were associated with a significant decrease in infectious diseases disseminated through airborne or fecal–oral transmission: common cold, gastroenteritis, bronchiolitis, and acute otitis. No change was found for urinary tract infections.